The Teaching and Learning on Speaking Skill: A Case Study at Seventh Grade VII F Students of SMPN 1 Kebonagung Pacitan - Samsul Hadi (Jurnal Penelitian Pendidikan, 2015)
This qualitative research was carried out in the classroom VII F of SMPN 1 KebonagungPacitan, on JLS Street Kebonagung Pacitan. The research was carried out at the firstsemester of the academic year of 2012/2013. Further, the techniques used to collectthe data were: (1) observation; (2) in-dept interview; (3) recording documents; (4)and then the data were documented. The data analysis was through seven steps thosewere: (1) observation; (2) textualisation; (3) multicolumn text; (4) segmentization; (5)thematization; (6) proposisionalization; (7) and reduction. The units of main data wereanalyzed by researcher through five steps which consisted of: being analyzed, beinginterpreted, being summarized, being concluded, and being recommended. Based on theresult on the observation in the activity of the teaching and learning speaking skill, itwas obtained 112 statements of data identities. In relation with the topic, some of thestatements of data identities were relevant but some others were not, the irrelevant datawere not discussed in this chapter (they were reduced), while the relevant data becameunits of main data analyzed based on the underlying theories and the result of interviews,as well as the related documents. The results and discussions include: (1) aspects oflearning done by the teachers including: methods were more atractive teacher-centeredand students-centered, teaching and giving instruction, teachers stood in front, thematerial presented was appropiate to the topic; (2) aspect of the students, among otherswere enthusiastic but tended to be crowded.